Individual Needs’ Influence On Retirement Intention: A Study Among Government Nurses In Malaysia - Visvanathan, Pakyasri (2022)
The study focuses on the retirement intention of government hospital nurses in Malaysia. Based on the self-determination theory, this study aims to understand the influence of individuals needs namely health, financial stability, individual career competency and work-life balance on retirement intention of the nurses. This is important as the Malaysian government hospital already faces the nurses’ shortages issue along with the increasing aging population that is nearing retirement age which leads to further loss of experienced nurses in government hospitals. Therefore, this study examines the influence of the four individual needs and the effect of employee characteristics on relationship between the individual needs and retirement intention of the government hospital nurses in Malaysia. A quantitative, and correlational research was adopted to evaluate all the hypotheses at 5% significance level via the usage of SPSS and PLS-SEM software. A purposive sampling method was used to collect three hundred and ninety-eight (398) samples. The findings resulted that out of four individual needs, only three; financial stability, individual career competency and work-life balance positively influenced retirement intention of government hospital nurses in Malaysia. While health needs had no positive influence on retirement intention. The moderating variable, employee characteristics was found not to moderate the relationship between the four individual needs and retirement intention. All these findings provide key insights that contributes to the self-determination theory in perspective of government hospital nurses in Malaysia.